Development of a prediction model and estimation of cumulative risk for upper aerodigestive tract cancer on the basis of the aldehyde dehydrogenase 2 genotype and alcohol consumption in a Japanese population. Issue 1 (January 2017) - Koyanagi, Yuriko N.; Ito, Hidemi; Oze, Isao; Hosono, Satoyo; Tanaka, Hideo; Abe, Tetsuya; Shimizu, Yasuhiro; Hasegawa, Yasuhisa; Matsuo, Keitaro
Abstract : Alcohol consumption and the aldehyde dehydrogenase 2 ( ALDH2 ) polymorphism are associated with the risk of upper aerodigestive tract cancer, and a significant gene–environment interaction between the two has been confirmed in a Japanese population. To aid the development of a personalized prevention strategy, we developed a risk-prediction model and estimated absolute risks stratified by a combination of the ALDH2 genotype and alcohol consumption. We carried out two age-matched and sex-matched case–control studies: one (630 cases and 1260 controls) for model derivation and the second (654 cases and 654 controls) for external validation. On the basis of data from the derivation study, a prediction model was developed by fitting a conditional logistic regression model using the following predictors: age, sex, smoking, drinking, and the ALDH2 genotype. The risk model, including a combination of the ALDH2 genotype and alcohol consumption, provided high discriminatory accuracy and good calibration in both the derivation and the validation studies: C statistics were 0.82 (95% confidence interval 0.80–0.84) and 0.83 (95% confidence interval 0.81–0.85), respectively, and the calibration plots of both studies remained close to the ideal calibration line. Cumulative risks were obtained by combining odds ratios estimated from the risk model with the age-specific incidence rate and population size. For heavy drinkers with a heterozygous genotype, the cumulative risk at age 80 was above 20%. In contrast, risk in the other groups was less than 5%. In conclusion, modification of alcohol consumption according to the ALDH2 genotype will have a major impact on upper aerodigestive tract cancer prevention. These findings represent a simple and practical model for personalized cancer prevention. Abstract : Supplemental Digital Content is available in the text.